2024
DOI: 10.1039/d3im00050h
|View full text |Cite
|
Sign up to set email alerts
|

Acetalization strategy in biomass valorization: a review

Abstract: Acetalization represents an appealing approach for the valorization of bio-based platform molecules into valuable chemicals and fuels. Typically, it serves as both a synthesis tool for renewable cyclic acetals, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 169 publications
0
5
0
Order By: Relevance
“…An acetalization strategy was developed for the upgradation of furanic compounds into fuel additives. 118 He et al designed a catalyst-free acetalization method to produce oxygenated fuel additives, 2-(furan-2-yl)-1,3-dioxolane, from renewable furfural and ethylene glycol (Scheme 16c). 119 78.6% yield was obtained in neat cyclohexane at 160 °C after 2 h. It was found that the overused ethylene glycol in this system enables recovery and reutilization without the loss of reaction activity.…”
Section: Upgradation Of Biomass-derived Moleculesmentioning
confidence: 99%
“…An acetalization strategy was developed for the upgradation of furanic compounds into fuel additives. 118 He et al designed a catalyst-free acetalization method to produce oxygenated fuel additives, 2-(furan-2-yl)-1,3-dioxolane, from renewable furfural and ethylene glycol (Scheme 16c). 119 78.6% yield was obtained in neat cyclohexane at 160 °C after 2 h. It was found that the overused ethylene glycol in this system enables recovery and reutilization without the loss of reaction activity.…”
Section: Upgradation Of Biomass-derived Moleculesmentioning
confidence: 99%
“…The acetalization/ketalization of glycerol has been studied under different conditions and catalysts. The cyclic acetals and ketal products obtained with aldehydes and ketones, respectively, present a large variety of applications [36]. One of the most desired is solketal, being a renewable raw material, obtained from glycerol by an acid-catalyzed reaction with acetone [12].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis is an important thermochemical route to convert bulky biomass to biochar and bio-oil of much higher volumetric energy density as well as pyrolytic gases that can be combusted in situ. [1][2][3] Biochar has versatile applications, while bio-oil is commonly accepted as an intermediate product for production of biofuel via further hydrotreatment. [4][5][6] However, owing to the high oxygen content, high acidity and high reactivity of the organics in bio-oil towards polymerization, hydrotreatment of bio-oil for deoxygenation is rather challenging due to rapid coking and deactivation of the catalyst, making the process costly.…”
Section: Introductionmentioning
confidence: 99%